1997
DOI: 10.1007/s004649900489
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for synchronous common bile duct stones in patients with cholelithiasis

Abstract: Multivariate logistic regression analysis on these significant predictors showed that cholangitis (odds ratio [OR]: 10.5), dilated CBD with evidence of stones on ultrasound (OR: 7.4), elevated aspartate transaminase (OR: 2.9), and conjugated bilirubin (OR: 5.3) were jointly significant. The likelihood of having stones in the duct without any of these predictors was 7%, but 99% when all the predictors were positive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
2
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 21 publications
3
39
2
2
Order By: Relevance
“…Diagnosis of common bile duct stones diagnosed. Higher NPV means then higher sensitivity for excluding CBDS as shown in our study; combining several tests in our study increased the negative predictive value and sensitivity of CBDS exclusion with almost equal specificity [16][17][18]30] . We concluded that patients with normal ultrasonography, LFT results and no clinical evidence of CBDS "negative triple test" (NPV of 97.3%) may undergo laparoscopic surgery without any need for preoperative MRCP or ERCP.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Diagnosis of common bile duct stones diagnosed. Higher NPV means then higher sensitivity for excluding CBDS as shown in our study; combining several tests in our study increased the negative predictive value and sensitivity of CBDS exclusion with almost equal specificity [16][17][18]30] . We concluded that patients with normal ultrasonography, LFT results and no clinical evidence of CBDS "negative triple test" (NPV of 97.3%) may undergo laparoscopic surgery without any need for preoperative MRCP or ERCP.…”
Section: Discussionsupporting
confidence: 74%
“…There is thus a need for easy-performing, non-invasive, and reliable test modalities to diagnose or exclude CBDS, by which selected patients can benefit from ERCP, MRCP or other expensive investigations [13][14][15] . Earlier studies on some clinical, laboratory or radiological variables have been performed [16,17] . There is however, as far as we know, no study performed evaluating a combination of these investigating modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical, ultrasonographic, and serum chemistry data commonly acquired during patient evaluations are sensitive in 96% to 98% and specific in 40% to 75% of the patients for the determination of choledocholithiasis. [2][3][4] Therefore, when these indicators are used for the selection of patients for endoscopic retrograde cholangiopancreatography (ERCP), up to 75% of the patients have no common bile duct (CBD) stones found during the procedure. Even though ERCP is effective for the diagnosis and clearance of CBD stones, this procedure can be associated with patient discomfort, inconvenience, and complications.…”
Section: Discussionmentioning
confidence: 99%
“…1 Choledocholithiasis is detected in 8% to 20% of patients undergoing cholecystectomy. [2][3][4] Several options are available for the diagnosis and treatment of choledocholithiasis, but there is no consensus on the optimal management strategy for these patients. 5 The selection of diagnostic and treatment approaches depends on multiple factors, including the level of suspicion for choledocholithiasis, patient and physician preferences, resource availability, and the expertise of the surgeons, endoscopists, and radiologists.…”
Section: Discussionmentioning
confidence: 99%